Using Surveys to Compare the Publics and Decisionmakers Preferences for Urban Regeneration: The Venice Arsenale - Anna Alberini; Alberto Longo; Patrizia Riganti (Fondazione Eni Enrico Mattei (FEEM), 2006)
In this paper, we illustrate how surveys can be used to elicit the preferences of the public and of policymakers and city officials for regeneration projects at urban sites. Our methodology uses rating exercises, coupled with conjoint-choice stated preferences for the general public and with ranking exercises for the public officials and other stakeholders, and is then applied to investigate alternative reuses of the Venice Arsenale, Italy, and their economic, environmental and social impacts. One interesting feature of the conjoint choice questions for members of the public is that the responses to these questions can be used to estimate the social benefits of regeneration projects, i.e., how much people are willing to pay for these urban transformations. Another advantage of our approach is that it can be used seek and foster broader public participation into urban decisionmaking processes.
Keywords: R14; 330; Land Use; Decision-Making; Cleanup; Sustainable Development; Local Economic Development; Choice Experiments; Stadtsanierung; Entscheidung; Befragung; Venedig